The Damage Capacity of Mahanarva spectabilis (Distant, 1909) (Hemiptera: Cercopidae) Adults on Brachiaria ruziziensis Pasture - Tiago Teixeira Resende; Alexander Machado Auad; Marcy das Graças Fonseca; Fausto Souza Sobrinho; Dayane Ribeiro dos Santos; Sandra Elisa Barbosa da Silva (The Scientific World Journal)
The aim of this study was to determine the damage caused by adult Mahanarva spectabilis (Distant, 1909) (Hemiptera: Cercopidae) on Brachiaria ruziziensis (Germain & Evard) under field conditions. A total of 0, 4, 8, 12, or 16 M. spectabilis adults per plot were maintained for 6 days. Thereafter, the insects were removed from the plant, and the following parameters were evaluated: chlorophyll content, damage score, dry as well as fresh weights, percentage of shoots’ dry matter, and the forage’s ability to regrow. The chlorophyll content was significantly reduced; the damage score and percentage of dry matter in plants increased depending on the increased insect infestation density after 6 days of exposure. In contrast, no change was observed on the B. ruziziensis fresh and dry weights as well as the regrowth capacity depending on the M. spectabilis infestation densities. Attacks by 8 adult M. spectabilis per clump of B. ruziziensis with an average of 80 tillers for 6 days were sufficient to reduce the chlorophyll content and the functional plant loss index. This density can be a reference for spittlebug integrated management in Brachiaria.